"A Disarticulate Intersection of Parallels": The Pan Africanist Congress of Azania and the African Renaissance Philosophy. Issue 2 (3rd July 2019) - Kondlo, Kwandiwe
Abstract: One of the important philosophies which has dominated in South Africa, especially during the presidency of Thabo Mbeki (1999–2008), and which continues to be important even today, is the African Renaissance philosophy. In essence, it is about the renewal of Africa and, especially, her commitment to unity and common goals. It is also about shining the continental revival spotlight on the nexus between growth and development. The African Renaissance conceives of development as partnership-based, in the same way the pan- Africanism of the Pan Africanist Congress (PAC) does. The idea of an African Renaissance, old as it is, was given fresh impetus by former President Mbeki. His famous "I am an African" speech, delivered in Cape Town on May 8, 1996, on the occasion of the adoption of the new Constitution of South Africa, lifted the profile of the philosophy. The PAC's muted reaction to the African Renaissance continues to raise questions as to whether the PAC's pan-Africanism stands in contrast to the views, values, and goals espoused by the African Renaissance philosophy and its agenda. This article describes the situation as a disarticulate intersection of parallels as the pan-Africanism of the PAC and the African Renaissance cross paths without, however, engaging in dialogue.